2017
DOI: 10.2175/106143017x15023776270601
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Environmental Pollutants

Abstract: This annual review covers the literature published in 2016 on topics related to the occurrence and fate of emerging environmental pollutants in wastewater. Due to the vast amount of literature published on this topic, we have discussed only a portion of the quality research publications, due to limitation of space. The abstract search was carried out using Web of Science, and the abstracts were selected based on their relevance. In few cases, fulltext articles were referred to better understand new findings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…However, excessive fertilizer use on agricultural soils leads to inorganic N pollutants being released into surface and groundwater bodies [1,2]. Kumar and Padhye [3] reported that high amounts of NH 4 + concentration causes eutrophication. Nutrients applied to soils can be retained through sorption (Adsorption and absorption).…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive fertilizer use on agricultural soils leads to inorganic N pollutants being released into surface and groundwater bodies [1,2]. Kumar and Padhye [3] reported that high amounts of NH 4 + concentration causes eutrophication. Nutrients applied to soils can be retained through sorption (Adsorption and absorption).…”
Section: Introductionmentioning
confidence: 99%